Peramalan Kinerja Lapangan SNP Dengan Injeksi Air Menggunakan Metode Material Balance - Andre Albert Sahetapy Engel; Rachmat Sudibjo; Muhammad Taufiq Fathaddin (Penerbitan Universitas Trisakti, 2018)
The decline in production from of a field is the common problem in the oil and gas industry. One of the causes of the decrease in production is the decline of reservoir pressure. Based on the analisis result, it was found that SNP field had a weak water drive. The most dominant drive of the field was fluid expansion. In order to reduce the problem, a reservoir pressure maintenance effort was required by injecting water. In this research, the effect of water injection to reservoir pressure and cumulative production was analyzed. From the evaluation result, it was found that the existing inejection performance using one injection well to Zones A and B was not optimum. Because, the recovery factor was predicted to 29.11% only.By activating the four injection wells, the recoverty factor could be increase to 31.43%.